2005
DOI: 10.1139/x05-200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different forest management systems on plant species diversity in aFagus crenataforested landscape of central Japan

Abstract: To clarify how different forest management systems affect the diversity of understory vascular plant species at the plot level and the forest-type level, we examined a forested landscape originally occupied by primary Japanese beech, Fagus crenata Blume, in central Japan. The landscape is currently composed of four types of forest: primary F. crenata forest, shelterwood logged F. crenata forest, abandoned coppice forest, and coniferous plantation. Species richness per plot (α diversity) and in each forest type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…Shifts in species composition may be related to logging intensity (Bergstedt, Milberg 2001;Zenner et al 2006). For instance, Nagaike et al (2005) reported that restoring the species composition of clear-cut forests to that of primary forests in central Japan was difficult; while other studies have described anywhere from a limited response to rapid recovery of species composition in a range of forest types following various cutting methods and intensities (e.g. Schelleer, Mladenoff 2002; Kern et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Shifts in species composition may be related to logging intensity (Bergstedt, Milberg 2001;Zenner et al 2006). For instance, Nagaike et al (2005) reported that restoring the species composition of clear-cut forests to that of primary forests in central Japan was difficult; while other studies have described anywhere from a limited response to rapid recovery of species composition in a range of forest types following various cutting methods and intensities (e.g. Schelleer, Mladenoff 2002; Kern et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the effects of forest management practices on plant species diversity is important for achieving ecologically sustainable forest management [2]. Most of the forests that cover Japan's surface are managed; these include plantations, coppices, and selection or selectively cut forests [3]. The plant species diversity of these managed forests is thus important for maintaining, conserving, and restoring biodiversity in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…For example, forest stands with relatively higher species richness or diversity are not always much better for biodiversity, as undesirable species (e.g., invasive or exotic species), which frequently comprise a high proportion of early successional species [8,9], can contribute toward a marked increase in diversity [10][11][12]. A comprehensive understanding of plant species diversity, species composition, and the ecological traits of species (i.e., plant functional types [13]) is thus considered necessary in order to understand and evaluate the quality of biodiversity ( [3,6], but see [14]). …”
Section: Introductionmentioning
confidence: 99%
“…The existence of complex species composition and stand structure can reflect the sustainability of forest management [9], and different management styles often lead to differences in community structure and biodiversity [10,11]. Forest management operations such as logging, tending, planting, and picking (e.g., fruits of Chinese magnolia vine and blueberries) have seldom been studied comprehensively in China, and various forest management types have not been compared.…”
mentioning
confidence: 99%
“…Management directly or indirectly affects plant biodiversity and stand structure in the understory by negatively influencing species richness and modifying diversity [1,10]. In addition, this management of human activities often threatens plant biodiversity and animal habitat [19][20][21][22].…”
mentioning
confidence: 99%